Profitability, Investment Factors and Trading Volume Adjustment on Equity Risk Premium an Empirical Evidence from Nairobi Stock Exchange - George Shibanda; Tobias Olweny; Tabitha Nasieku (Journal of Accounting and Finance in Emerging Economies)
Purpose: Equity markets have always fascinated and challenged financial researchers with their complexities and broad implications. This Study investigated the effect of profitability measures and investment factors on the Equity Premium of companies listed on the Nairobi Securities Exchange (NSE) from 2011 to 2022.